Validation of a Simple Approach to Caries Risk Assessment - James D. Bader, DDS, MPH; Nancy A. Perrin, PhD; Gerard0 Maupome, BDS, MS, PhD, Brad Rindal, DDS; Wil (Blackwell Synergy, 2005)
This study examined the predictive validity of a simple subjective method promoted to dentists for assessing their patients’ caries risk.